Case study: Cinnamon aspiration in a toddler causing severe ARDS requiring surfactant and extracorporeal membrane oxygenation. Issue 1 (28th October 2021) - Peir, Gene Hwan; Boggs, Kaitlyn Maureen; Soto, Pelayia H.; Weinstock, Jered; Sharron, Matthew P.; Sami, Iman; Dean, Terry
Abstract: As many as 6% of reported cinnamon poisonings cause significant clinical effects, however, descriptions of pulmonary toxicity have not yet been reported. Here, we present a pediatric patient's hospital course following powdered cinnamon aspiration. The early presentation with hypercapnia and lower airways obstruction evolved to hypoxemic respiratory failure and severe pediatric acute respiratory distress syndrome requiring a 7‐day course of veno‐venous extracorporeal membrane oxygenation, 16 ventilator‐days, and three diagnostic and therapeutic bronchoscopies with two applications of surfactant therapy. The sum of these modalities contributed to this patient's survival and subsequent return to respiratory baseline 6 months post‐hospitalization.